2020
DOI: 10.1002/fsn3.2060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultra‐high pressure on the morphological and physicochemical properties of lily starch

Abstract: In this study, starch extracted from lily bulbs were modified using an ultra‐high pressure (UHP) treatment at six different pressure levels (100, 200, 300, 400, 500, and 600 MPa). The effects of UHP treatment on the physicochemical and morphological properties of lily starch were investigated. The morphological observation revealed that UHP treatment led to particle expansion and aggregation. Compared with the native and lily starch treated at 100–500 MPa, the lily starch treated at 600 MPa exhibited almost co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…The effects of high‐pressure treatment on starch crystalline property were summarised in Table S4 (Li et al ., 2011, 2012, 2015, 2018; Slominska et al ., 2015; Liu et al ., 2016a, 2016b, 2016c; Hu et al ., 2017; Ahmed et al ., 2018; Colussi et al ., 2018; Zhang et al ., 2019, 2021; Sandhu et al ., 2021; Almeida et al ., 2022; Bajaj et al ., 2021; Chen et al, 2022a, 2022b). In most studies, the relative crystallinity of starches all reduced to varying degrees after high‐pressure treatment.…”
Section: The Effects Of Pressure On Starch Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of high‐pressure treatment on starch crystalline property were summarised in Table S4 (Li et al ., 2011, 2012, 2015, 2018; Slominska et al ., 2015; Liu et al ., 2016a, 2016b, 2016c; Hu et al ., 2017; Ahmed et al ., 2018; Colussi et al ., 2018; Zhang et al ., 2019, 2021; Sandhu et al ., 2021; Almeida et al ., 2022; Bajaj et al ., 2021; Chen et al, 2022a, 2022b). In most studies, the relative crystallinity of starches all reduced to varying degrees after high‐pressure treatment.…”
Section: The Effects Of Pressure On Starch Propertiesmentioning
confidence: 99%
“…In most studies, the relative crystallinity of starches all reduced to varying degrees after high‐pressure treatment. For example, the relative crystallinity of potato starch and lily starch decreased from 19.1% and 38.2% to 14.6% and 8.1% after a 600 MPa treatment for 30 min (Colussi et al ., 2018; Zhang et al ., 2021). In addition, it was found that the A or C‐type crystal would change to B‐type after high‐pressure treatment (Li et al ., 2011, 2012, 2016; Hu et al ., 2017).…”
Section: The Effects Of Pressure On Starch Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the high number of free hydroxyl groups on the structure of starch, these compounds can be easily modified by physical, chemical, biotechnological, or enzymatic methods as well as their combination (Ashogbon, 2020 ). These modifications are done to improve the texture, adhesion, gel clarity, film making, cooking properties, transparency of gel, freeze‐thaw stability, reduction of retrogradation, the tendency to gel, and syneresis (Mehfooz et al., 2019 ; Zhang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high number of free hydroxyl groups on the structure of starch, these compounds can be easily modified by physical, chemical, biotechnological, or enzymatic methods as well as their combination (Ashogbon, 2020). These modifications are done to improve the texture, adhesion, gel clarity, film making, cooking properties, transparency of gel, freeze-thaw stability, reduction of retrogradation, the tendency to gel, and syneresis (Mehfooz et al, 2019;Zhang et al, 2021). Chemical modification of starch structure includes cross-linking, acid hydrolysis, oxidation, acetylation, grafting, esterification, and dual modification (Haq et al, 2019), which are most used in industry due to easier control (Araghi et al, 2015;Li et al, 2018).…”
mentioning
confidence: 99%